HUBUNGAN PERBANDINGAN TOTAL NITROGEN DAN TOTAL FOSFOR DENGAN KELIMPAHAN CHRYSOPHYTA DI PERAIRAN WADUK PANGLIMA BESAR SOEDIRMAN, BANJARNEGARA - Faralenggi DM Putri; Endang Widyastuti; Christiani Christiani (Fakultas Biologi | Universitas Jenderal Soedirman, 2014)
Nitrogen (N) and phosphorus (P) affect the growth of phytoplankton in the waters. Nitrogen is an important part in forming protein in organisms, while phosphorus is the most essential element for growth and contributes in protein formation and cell metabolism in organisms. The activities from the catchment area that enter into the P.B Soedirman Reservoir can affect both concentration of N and P. The comparison total nitrogen (TN) and total phosphorus (TP) is the limiting factor to affect the growth of phytoplankton. Chrysophyta is one of division from phytoplankton that has function as an important component in the food chain and become as natural feed for fish. This research showed the abundance of Chrysophyta, relations of TN with the abundance of Chrysophyta; TP with the abundance of Chrysophyta; TN/TP with the abundance of Chrysophyta; TN, TP, TN/TP with the abundance Chrysophyta in the P.B Soedirman Reservoir, Banjarnegara Regency. This research used survey method with purposive sampling technique on 7 observation stations with 3 repeating. The relation of TN/TP with the abundance of Chrysophyta were analyzed used correlation regression - correlation analyzis. The results of the research showed that total abundance Chrysophyta was between 339-9570 ind/l, relation between TN/TP with the abundance of Chrysophyta with the degree was weak to very strong correlation. The most affection correlation was shown by of TN, TP, TN/TP collectively with the abundance of Chrysophyta with coefficient value (r) of 0,890 with the strength of the relation of 79,3%. The regression analysis of TN, TP, TN/TP collectively with the abundance of Chrysophyta was shown by the equation Y= – 80987,801 – 8499,931TN + 1,684TP + 406,373TN/TP.